El papel social de la publicidad - Codeluppi, Vanni (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
This paper analyses the behavior of advertising and the limites society tries to impose over it. This cogitation is made from a sociological perspective, due to the fact that it deals with the effects that advertising generates over social contexts and not over individual consumers.